Enhanced visceromotor emotional reactivity in dyslexia and its relation to salience network connectivity. (January 2021) - Sturm, Virginia E.; Roy, Ashlin R.K.; Datta, Samir; Wang, Cheng; Sible, Isabel J.; Holley, Sarah R.; Watson, Christa; Palser, Eleanor R.; Morris, Nathaniel A.; Battistella, Giovanni; Rah, Esther; Meyer, Marita; et al.
Abstract: Dyslexia is a neurodevelopmental disorder mainly defined by reading difficulties. During reading, individuals with dyslexia exhibit hypoactivity in left-lateralized language systems. Lower activity in one brain circuit can be accompanied by greater activity in another, and, here, we examined whether right-hemisphere-based emotional reactivity may be elevated in dyslexia. We measured emotional reactivity (i.e., facial behavior, physiological activity, and subjective experience) in 54 children ages 7–12 with ( n = 32) and without ( n = 22) dyslexia while they viewed emotion-inducing film clips. Participants also underwent task-free functional magnetic resonance imaging. Parents of children with dyslexia completed the Behavior Assessment System for Children, which assesses real-world behavior. During film viewing, children with dyslexia exhibited significantly greater reactivity in emotional facial behavior, skin conductance level, and respiration rate than those without dyslexia. Across the sample, greater emotional facial behavior correlated with stronger connectivity between right ventral anterior insula and right pregenual anterior cingulate cortex ( p FWE <.05), key salience network hubs. In children with dyslexia, greater emotional facial behavior related to better real-world social skills and higher anxiety and depression. Our findings suggest there is heightened visceromotor emotional reactivity in dyslexia, which may lead to interpersonal strengths as well as affective vulnerabilities.